2015
DOI: 10.1111/jphd.12082
|View full text |Cite
|
Sign up to set email alerts
|

Screening for prediabetes and type 2 diabetes in dental offices

Abstract: ObjectivesMost Americans see dentists at least once a year. Chair‐side screening and referral may improve diagnosis of prediabetes and diabetes. In this study, we developed a multivariate model to screen for dysglycemia (prediabetes and diabetes defined as HbA1c ≥5.7 percent) using information readily available to dentists and assessed the prevalence of dysglycemia in general dental practices.MethodsWe recruited 1,033 adults ≥30 years of age without histories of diabetes from 13 general dental practices. A sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 31 publications
3
91
2
2
Order By: Relevance
“…Because periodontal disease is associated with diabetes, the utility of chairside screening and referral to primary care as a means to improve the diagnosis of prediabetes and diabetes has been explored (39-41), with one study estimating that 30% of patients $30 years of age seen in general dental practices had dysglycemia (41). Further research is needed to demonstrate the feasibility, effectiveness, and cost-effectiveness of screening in this setting.…”
Section: Screening In Dental Practicesmentioning
confidence: 99%
“…Because periodontal disease is associated with diabetes, the utility of chairside screening and referral to primary care as a means to improve the diagnosis of prediabetes and diabetes has been explored (39-41), with one study estimating that 30% of patients $30 years of age seen in general dental practices had dysglycemia (41). Further research is needed to demonstrate the feasibility, effectiveness, and cost-effectiveness of screening in this setting.…”
Section: Screening In Dental Practicesmentioning
confidence: 99%
“…A sample of participants then went on to receive a definitive diagnosis using A1c information. The results showed that patients at risk of prediabetes or diabetes could be identified rapidly using the risk questions alone or with the random capillary glucose test (Herman, Taylor, Jacobson, Burke, & Brown, 2015). This study did not go beyond identifying those at risk of diabetes and the HbA1c test was not administered during the dental visit.…”
Section: Patients' Views On Screening For Diabetes In Dental Settingsmentioning
confidence: 93%
“…Herman et al [27] suggested many Americans see a dentist at least once a year, which is not the case in our community dental clinic patients, who often have to wait a considerable amount of time on the waiting list for any dental procedures including initial dental examination (up to 2 years). Herman et al [27] introduced dysglycemia screening in 13 general dental practices using a questionnaire similar to the AUSDRISK tool and identified 30% of patients in a high risk diabetes category, considerably lower than our 52% at a high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the USA report a prediabetic HbA1c range as 5.7% to 6.4% and suggest people with HbA1c > 6.4% on more than one reading has diabetes [27,28]. Genco et al [28] investigated the utility of screening for diabetes in dental settings and concluded forty percent had an HbA1c level of greater than 5.7% and were referred on for further diagnosis with 12% confirmed and 23% with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation